Faktor- Faktor Yang Berhubungan Dengan Kejadian Preeklamsia Berat Pada Ibu Bersalin di RS Medika Dramaga Bogor: Factors Associated with the Incidence of Severe Preeclampsia in Maternal Maternity at Medika Hospital Dramaga Bogor - Siti Syamsiah; Rahayu Putri; Anni Suciawati (Open Access Jakarta Journal of Health Sciences, 2022)
Background: PEB is one of the causes of maternal death. The aetiological approach is the best way to reduce maternal mortality and morbidity due to severe preeclampsia which is influenced by several factors, including age, parity, history of hypertension, education, occupation. Based on medical records at the Medika Dramaga Hospital, Bogor, the incidence of severe preeclampsia from 2017-2018 there was an increase of about 6% in the incidence of severe preeclampsia. Objective: To determine the factors associated with the incidence of severe preeclampsia in women giving birth at the Medika Dramaga Hospital, Bogor in 2019. Methods: This study uses secondary data with analytical descriptive research methods and the design is cross-sectional. The study was conducted in 2019 and the population was 200 with the sample in this study totaling 99 samples of mothers giving birth using the Purposive Sampling Systematic Technique. The analysis used is univariate and bivariate. Results: The results of the study of 99 women who had severe preeclampsia were 51 women who gave birth (51.5%) and who did not experience severe preeclampsia were 48 women who gave birth (48.5%). Maternal mothers aged 20 and 35 years were 54 people (54.5%). There were 51 mothers giving birth with multigravida parity (51.5%). Maternity mothers with higher education were 62 people (62.6%). Maternity mothers who did not work were 59 people (59.6%). Maternal mothers who had a history of hypertension were 50 maternity mothers (50.5%). Conclusion: The statistical test of the variables showed a relationship, namely Age (P-Value = 0.0012, OR = 3.764), History of Hypertension (P-Value = 0.000, OR = 5.829). And there is no relationship between the variables Parity (P-Value = 0.913, OR = 1.045), Education (P-Value = 0.222, OR = 1.669), Employment (P-Value = 0.568, OR = 1.264).